Work Motivation among Muslim Healthcare Employees in Pattani Province, Thailand - Emeela Wae-esor; Azizi Bin Abu Bakar; Hoe Chee Hee (International Journal of Supply Chain Management, 2016)
Pattani is a province with a multi-ethnic population which the majority is Muslim. As such, employers in this region need a good understanding of how employees behave and work in such an environment of employees dissimilarity in order to ensure the fulfilment of employees work motivation. This study aims to determine alternative factors which impact work motivation to support and develop a conceptual framework of work motivation among Muslim public health employees in Pattani Province. The conceptual model for this study posits that work motivation is dependent on the two independent variables, namely; a) Islamic Workplace Accommodation; b) Nature of Work. A questionnaire survey of 242 Muslim employees from Public Health Center in Pattani province showed that that the relationship between the Islamic Workplace Accommodation and Nature of Work are positive toward Work Motivation.